Death of American Empire - Sirohey, A. A. (Lahore Al-Asr Publications, 2008)
This book is obviously a new chapter on crumbling capitalist empire where a sitting President is accused of causing death of his own state. he has opened a widow to see through the fall and demise of the powerful nation in the world.
Include Graphs and Bibliography.
This work is a collection of essays relating to social and economic, leadership, and ethics, ecological and religious issues that are facing the world today in order to understand the course of history that has led humanity to its present condition and then arrive at positive solutions that will lead to better outcomes for all humanity
Keywords: United States -- Diplomatic relations -- Politics and government -- Economic history